Pesquisas sobre hip hop: mutilação e abordagem narrativa - Zibordi, Marcos (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article summarizes findings regarding the mutilation of the research object called hip hop work in undergraduate, master's and doctoral performed in three major public universities in São Paulo, University of São Paulo (USP), University of Campinas (Unicamp) and Universidade Estadual Paulista (UNESP). After epistemological analysis of the academic literature, the article indicates two theoretical concepts that supported the characterization of the elements of hip hop as narratives.
Keywords: Epistemology; Hip hop; Narrative